Pathophysiology of diabetic retinopathy - Cunha-Vaz, JG (2011)
After a brief analysis of the pathological picture of diabetic retinopathy, of which only the topographical distribution of the vascular lesions appears to be specific, the results obtained with 2 new methods of study of the retinal circulation, are presented. These methods are vitreous fluorophotometry and fluorometric determination of segmental retinal blood flow. Vitreous fluorophotometry has shown that a disturbance of the blood-retinal barrier, possibly functional, appears in diabetic eyes before any lesion is clinically visible in the fundus, and that there is a close correlation between the severity of the vascular lesions and higher vitreous fluorophotometry readings. Blood flow studies have shown that in diabetes the retinal blood flow increases markedly with progress of background retinopathy, decreasing finally where proliferative retinopathy, with marked arteriolar narrowing, is present. On the basis of these findings a working hypothesis for the pathogenesis of diabetic retinopathy is presented.